2018
DOI: 10.1088/1361-648x/aabe52
|View full text |Cite
|
Sign up to set email alerts
|

Role of zero-point effects in stabilizing the ground state structure of bulk Fe2P

Abstract: Structural stability of FeP is investigated in detail using first-principles calculations based on density functional theory. While the orthorhombic C23 phase is found to be energetically more stable, the experiments suggest it to be hexagonal C22 phase. In the present study, we show that in order to obtain the correct ground state structure of FeP from the first-principles based methods it is utmost necessary to consider the zero-point effects such as zero-point vibrations and spin fluctuations. This study de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 43 publications
3
21
0
Order By: Relevance
“…However, the authors did not provide the details of their calculations. DFT calculations carried out by Bhat et al 29 showed that C22/C23 phase www.nature.com/scientificreports www.nature.com/scientificreports/ transition occurred at about 300 K indicating that C23-allabogdanite can be stable at ambient conditions. The use of DFT + U approach also led to the stability of allabogdanite 29 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the authors did not provide the details of their calculations. DFT calculations carried out by Bhat et al 29 showed that C22/C23 phase www.nature.com/scientificreports www.nature.com/scientificreports/ transition occurred at about 300 K indicating that C23-allabogdanite can be stable at ambient conditions. The use of DFT + U approach also led to the stability of allabogdanite 29 .…”
Section: Discussionmentioning
confidence: 99%
“…DFT calculations carried out by Bhat et al 29 showed that C22/C23 phase www.nature.com/scientificreports www.nature.com/scientificreports/ transition occurred at about 300 K indicating that C23-allabogdanite can be stable at ambient conditions. The use of DFT + U approach also led to the stability of allabogdanite 29 . Finally, considering the energy contribution of zero-point spin fluctuations (ZPSF) Fe 2 P-barringerite phase became energetically favorable, which, according to the authors, represents the exceptionally rare case of bulk material stabilization 29 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In zero applied field (ZF), 31 P and 57 Fe nuclei resonate in their hyperfine fields, giving rise to distinct resonance lines for each crystallographic site. We detected the 57 Fe resonance stemming from Fe2 and the 31 P resonances of P1 and P2 and unambiguously assigned them to their respective nuclei, thus correcting the peak attribution by an early NMR work [23], which is proven here to be erroneous.…”
Section: Introductionmentioning
confidence: 99%